(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of morbidity and mortality worldwide. Structural and functional changes in the airways often precede the onset of symptoms, resulting in delayed diagnosis. Early identification of airflow limitation among smokers may facilitate timely intervention and smoking cessation. Spirometry is a simple, non-invasive, and reliable tool for detecting early airflow obstruction. Aim: To evaluate the role of spirometry in the early detection of Chronic Obstructive Pulmonary Disease among asymptomatic smokers. Methods: A hospital-based cross-sectional study was conducted among 72 asymptomatic smokers aged 30 years and above with a smoking history of at least 10 pack-years. Demographic details and smoking characteristics were recorded using a structured questionnaire. All participants underwent spirometric evaluation according to American Thoracic Society and European Respiratory Society guidelines. Airflow obstruction was defined as a post-bronchodilator FEV₁/FVC ratio of less than 0.70. Data were analyzed using SPSS software, and associations were assessed using appropriate statistical tests. Results: The mean age of the participants was 46.8 ± 10.7 years, and 91.7% were males. Spirometry detected airflow obstruction suggestive of COPD in 10 (13.9%) participants despite the absence of respiratory symptoms. Among those with airflow obstruction, 60% were classified as GOLD stage I and 40% as GOLD stage II. The mean FEV₁/FVC ratio was 75.8 ± 7.1%. A significant association was observed between smoking exposure and airflow obstruction, with smokers having ≥30 pack-years showing a higher prevalence of COPD compared to those with lower smoking exposure (p = 0.018). Conclusion: Spirometry is an effective screening tool for the early detection of COPD among asymptomatic smokers. Routine spirometric assessment in high-risk smokers may facilitate early diagnosis, smoking cessation counseling, and timely intervention, thereby reducing future disease burden.